Sexual Harassment and Objectivity: Why We Need Not Ask Women If They Are Victims - Tomasello, Jenna (Stance: an international undergraduate philosophy journal, 2013)
Sexual harassment is often understood as a subjective notion that asks the woman if she has been victimized. This paper argues that we need not ask women if they are victims by conceptualizing sexual harassment as an objective notion that holds the perpetrator accountable for his actions. In making my case, I will apply an objective conception of sexual harassment to the U.S. Supreme Court case Meritor Savings Bank v. Vinson by drawing on the feminist view of sexual harassment given by Anita Superson and the role of equality and autonomy as motivated by Ronald Dworkin and James Griffin, respectively.